Design and evaluation of cost-effective oro-dispersible tablets of venlafaxine hydrochloride by effervescent method - Mahale, Sunita; Tayde, Manisha; Ahire, Yogita G; Dhikale, Rupali S; Gulecha, Vishal S (Creative Pharma Assent, 2024)
Background: Venlafaxine hydrochloride (VFH) is an antidepressant drug with poor bioavailability due to extensive first-pass metabolism. Objective: In the present study, oro-dispersible VFH tablets were prepared using an effervescent method to enhance patient compliance using a design of experiment (DoE) approach. Methods: A two-factor, three-level 32 full factorial design was applied to investigate the combined effect of two formulation variables: the amount of treated agar and effervescent material (mixture of sodium bicarbonate, citric acid and tartaric acid) on disintegration time and %drug release (Critical quality attributes). Treated agar (12-18%w/w) was used as a disintegrant, and a mixture of sodium bicarbonate, citric acid and tartaric acid (12-16%w/w) was used as effervescent material along with directly compressible excipients to enhance mouth feel. The association between the factors and responses was established by plotting response surfaces and contour plots. A 3D surface plot was used further to evaluate the responses to the factors. Prepared tablets were evaluated for wetting time, hardness, friability, thickness, drug content uniformity, and disintegration time. In vitro, drug release studies and stability studies were also performed. Results: The tablet formulation containing 17.5% w/w treated agar and 16%w/w mixture of sodium bicarbonate, citric acid and tartaric acid was found to be a promising formulation with a disintegration time of 27 seconds and in vitro drug release of 97.38% (in phosphate buffer of pH 6.8). Conclusion: The use of effervescent material was found to be useful for taste masking as well as patient compliance.